Exploring welfare, organizational commitment, and turnover intention: An empirical investigation of Indonesian Air Force pilot - Budi Santoso; Haliansyah Haliansyah (Annals of Management and Organization Research, 2025)
Purpose: This study aims to investigate how organizational commitment and welfare affect the likelihood of pilots leaving the Indonesian Air Force. It examines whether organizational commitment acts as a bridge between welfare and turnover intention. The goal is to provide insights into improving pilot retention, ensuring operational readiness and national security. Methodology: Research design employs a quantitative research approach using Structural Equation? Modeling (SEM) PLS to analyze the relationships between welfare, organizational commitment, and turnover intention among Indonesian Air Force pilots. Data were collected through a survey questionnaire distributed to active-duty pilots. Results: Findings indicate that welfare and organizational commitment both significantly reduce turnover intention. Affective commitment (emotional attachment to the organization) is the strongest factor in reducing turnover intention. Better welfare policies, such as job satisfaction programs, improve organizational commitment, further lowering turnover rates. Conclusions: Enhancing welfare policies and organizational commitment can help retain skilled pilots. The Indonesian Air Force should focus on comprehensive welfare programs and engagement strategies to strengthen pilots' commitment and reduce turnover. Limitations: This study only examines organizational commitment and welfare. Other factors, like leadership styles and career development opportunities, were not considered. Contribution: This research helps military policymakers and organizational leaders understand how to improve pilot retention. It contributes to studies on employee retention in high-risk professions and provides practical recommendations for enhancing workforce stability.